2016
DOI: 10.3109/09638288.2015.1114156
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professional experiences with patients who participate in multimodal pain rehabilitation in primary care – a qualitative study

Abstract: PurposeExploring healthcare professional experiences of Multimodal rehabilitation (MMR) in primary care. MethodsFourteen healthcare professionals (11 women, 3 men) were individually interviewed about their work with MMR in primary care. Interviews covered experiences of assessing patients and work with patients in the program. Transcribed interviews were analysed by qualitative content analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Some previous studies found that women were selected for MMRP more often than men (28). Qualitative interviews conducted in the same settings in primary care indicate that healthcare professionals were hesitant to refer single men to an MMRP (29).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some previous studies found that women were selected for MMRP more often than men (28). Qualitative interviews conducted in the same settings in primary care indicate that healthcare professionals were hesitant to refer single men to an MMRP (29).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, further development of MMRP is warranted in order to improve the outcomes. Although national guidelines were published to support the assessment of patients with chronic pain with selection criteria to enhance MMRP at the appropriate level (specialist vs primary healthcare), healthcare professionals in primary care found it difficult to select patients for MMRP (29).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that MMR team personnel expressed fear of not adequately investigating the patient and they were afraid they might have missed a serious medical condition (12). This attitude increases the chance that a patient is referred for a wide variety of assessments and will get different solutions suggested for solving the pain.…”
Section: Discussionmentioning
confidence: 99%
“…Professional experiences of working with MMR showed that it sometimes was difficult to get enough participants in a group. They wondered why all patients who seek care for chronic pain were not referred to MMR (12). This might be because MMR was a new intervention in primary care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation